2011
DOI: 10.5194/acp-11-67-2011
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced volatility of molecular markers in ambient airborne particulate matter

Abstract: Abstract. Molecular markers are organic compounds used to represent known sources of particulate matter (PM) in statistical source apportionment studies. The utility of molecular markers depends on, among other things, their ability to represent PM volatility under realistic atmospheric conditions. We measured the particle-phase concentrations and temperature-induced volatility of commonly-used molecular markers in California's heavily polluted San Joaqin Valley. Concentrations of elemental carbon, organic car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…On the other hand, warmer months' concentrations were 7.3±1.5 ng/m 3 and 7.9±1.6 ng/m 3 , indicating about 2 fold increase in colder months period in both sites. The lower levels of n-alkanes during warmer months could be due to volatilization of particulate phase into gas phase (Ruehl et al, 2011). Furthermore, the elevated concentration in colder months can be attributed to the lower atmospheric mixing height in the winter that limited dilution of total n-alkanes, in addition to the increased source strengths of these species in the winter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, warmer months' concentrations were 7.3±1.5 ng/m 3 and 7.9±1.6 ng/m 3 , indicating about 2 fold increase in colder months period in both sites. The lower levels of n-alkanes during warmer months could be due to volatilization of particulate phase into gas phase (Ruehl et al, 2011). Furthermore, the elevated concentration in colder months can be attributed to the lower atmospheric mixing height in the winter that limited dilution of total n-alkanes, in addition to the increased source strengths of these species in the winter.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of laboratory studies that have suggested that some of the tracers used in the current model are semi-volatile and reactive and may not be suitable for use as source tracers (May et al, 2012; Ruehl et al, 2011). However, a comparison of source apportionment methods using real world data sets have shown good agreement across CMB, PMF, and UNMIX, which would not be expected if the key tracers for these sources (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The monosaccharide anhydrides (MAs) levoglucosan, galactosan and mannosan are products of the incomplete combustion and pyrolysis of cellulose and hemicelluloses, and are thus constituents of biomass burning (BB) aerosol (Hornig et al, 1985;Simoneit, 1999). The presence of MAs has been demonstrated in emissions from wood combustion (Oros and Simoneit, 1999;Fine et al, 2001;Nolte et al, 2001;Schmidl et al, 2008;Frey et al, 2009;Gonçalves et al, , 2011Orasche et al, 2012) as well as from wildfires, prescribed and agricultural fires (dos Santos et al, 2002;Gao et al, 2003;Sillanpää et al, 2005;Mazzoleni et al, 2007;Sullivan et al, 2008;Alves et al, 2010;Saarnio et al, 2010a;Vicente et al, 2012;Wang et al, 2011). Recently, it has been shown that combustion of peat (Iinuma et al, 2007;Kourtchev et al, 2011) as well as of certain types of brown coal (Fabbri et al, 2009) could be additional sources of ambient aerosol concentrations of MAs in regions where such fuels are utilised.…”
Section: Introductionmentioning
confidence: 99%
“…Species in OC2 may contain carboxylic acids, polyaromatic hydrocarbons (PAHs), and steranes . PAHs and steranes are anthropogenic emissions markers for incomplete fossil fuel combustion and motor oil emissions, and carboxylic acids originate from oxidation of biogenic and anthropogenic VOCs or direct emission from fossil fuel combustion and biomass burning . Changes in PC may be due to misapportioned EC, and some laboratory analyses connect PC to WSOC .…”
Section: Resultsmentioning
confidence: 99%